Functional characteristics of zooplankton bioregions along the cross-shelf gradient - Patrick R. Pata; Moira Galbraith; Kelly Young; Akash R. Sastri; R. Ian Perry; Brian P.V. Hunt (Progress in Oceanography, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Dust in the Critical Zone: North American case studies - J. Brahney; R.C. Heindel; T.E. Gill; G. Carling; J.M. González-Olalla; J. Hand; D.V. Mallia; J.S. Munroe; K. Perry; A.L. Putman; S.M. Skiles; B.R. Adams; et al. (Earth-Science Reviews, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Seasonal and regional variability of model-based zooplankton biomass in the Salish Sea and evaluation against observations - Karyn D. Suchy; Elise Olson; Susan E. Allen; Moira Galbraith; BethElLee Herrmann; Julie E. Keister; R. Ian Perry; Akash R. Sastri; Kelly Young (Progress in Oceanography, 2023)

Match/Mismatch Between Phytoplankton and Crustacean Zooplankton Phenology in the Strait of Georgia, Canada - Karyn D. Suchy; Kelly Young; Moira Galbraith; R. Ian Perry; Maycira Costa (Frontiers in Marine Science, 2022)
The Strait of Georgia, Canada, is an important region for numerous commercially and culturally important species (e.g., herring, salmon, and orcas), yet little is known about the links between lower trophic level (e.g. phytoplankton and zooplankton) phenology due to historical sampling gaps. Here, we present fourteen years (2003-2016) of data linking interannual variability in phytoplankton and zooplankton phenology in the Central Strait of Georgia, BC. Satellite-derived chlorophyll a (Chl a ) data were used to calculate spring bloom dynamics (bloom initiation, bloom intensity, and bloom magnitude). Average spring bloom initiation occurred during the last week of March in the Central Strait of Georgia. Bloom initiation occurred in mid-to-late February/early March during “early” Chl a bloom years (2004, 2005, and 2015) whereas initiation did not occur until the end of April during “late” bloom years (2007, 2008). Spring Chl a bloom initiation was significantly correlated with the North Pacific Gyre Oscillation (NPGO; r = 0.75, p < 0.01) and spring sea surface temperature (SST; r = -0.70, p < 0.01); spring blooms occurred earlier during warm years. When all environmental variables were considered together, NPGO best explained variations in spring bloom initiation (Adj R 2 = 0.53, p < 0.01) and bloom magnitude (Adj R 2 = 0.57, p < 0.01), whereas stratification best explained variations in bloom intensity (Adj R 2 = 0.38, p < 0.05). Early Chl a blooms were associated with high crustacean abundance (maximum of > 1000 ind m -3 ) but low biomass (37.5 mg m -3 ). Independent of the Chl a data, hierarchical cluster analysis revealed similar groupings of years for crustacean abundance data. Most notably, community composition in cluster Group 2 (2004, 2005, and 2015; early Chl a bloom years), was comprised of a higher proportion of small crustaceans (e.g. non-calanoid copepods) compared to the other cluster groups. To our knowledge, this study provides the first evidence linking early spring Chl a bloom timing to a shift in the crustacean community towards smaller taxa in response to multiple warm events in the Strait of Georgia. Our results show that early Chl a blooms may potentially result in a mismatch between phytoplankton and large energy-rich crustacean zooplankton, with lower abundances of the latter. In contrast, average Chl a bloom years were optimal for large-bodied euphausiids, whereas late Chl a blooms were a match for some crustaceans (e.g., medium calanoid copepods), but not others (e.g., large calanoid copepods and amphipods). We hypothesize that early bloom years may result in poorer feeding conditions for juvenile salmon and other predators in the region.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Assessing Potential Risk to Alligators, Alligator mississippiensis, from Nutria Control with Zinc Phosphide Rodenticide Baits - Gary W. Witmer; John D. Eisemann; Thomas M. Primus; Jeanette R. O’Hare; Kelly R. Perry; Ruth M. Elsey; Phillip L. Trosclair (Bulletin of Environmental Contamination and Toxicology, 2010)

Deer Responses to Repellent Stimuli - Bruce A. Kimball; Jimmy Taylor; Kelly R. Perry; Christina Capelli (Journal of Chemical Ecology, 2009)

Manipulating Beaver (Castor canadensis) Feeding Responses to Invasive Tamarisk (Tamarix spp.) - Bruce A. Kimball; Kelly R. Perry (Journal of Chemical Ecology, 2008)

In vivo pharmacological characterization of the structurally novel, potent, selective mGlu2/3 receptor agonist LY404039 in animal models of psychiatric disorders - Linda M. Rorick-Kehn; Bryan G. Johnson; Karen M. Knitowski; Craig R. Salhoff; Jeffrey M. Witkin; Kenneth W. Perry; Kelly I. Griffey; Joseph P. Tizzano; James A. Monn; David L. McKinzie; Darryle D. Schoepp (Psychopharmacology, 2007)